2009
DOI: 10.1111/j.1365-2133.2009.09576.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous B-cell lymphoma is associated with somatically hypermutated immunoglobulin variable genes and frequent use of VH1-69 and VH4-59 segments

Abstract: Data indicate that neoplastic B cells of PBCBL have experienced germinal centre reaction and also suggest that the involvement of IgVH genes is not entirely random in PCBCL and that common antigen epitopes could be pathologically relevant in cutaneous lymphomagenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 44 publications
0
15
1
Order By: Relevance
“…This observation contrasts with the concept that MALT lymphoma is derived from postgerminal center memory B cells [1]. It has been reported that MALT lymphomas of the stomach [12], ocular adnexae [20], and skin [21] usually possess mutated VH genes. However, frequently unmutated genes have been reported in salivary [18] and thymic [19] MALT lymphomas as well as splenic marginal zone lymphoma [23].…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…This observation contrasts with the concept that MALT lymphoma is derived from postgerminal center memory B cells [1]. It has been reported that MALT lymphomas of the stomach [12], ocular adnexae [20], and skin [21] usually possess mutated VH genes. However, frequently unmutated genes have been reported in salivary [18] and thymic [19] MALT lymphomas as well as splenic marginal zone lymphoma [23].…”
Section: Discussioncontrasting
confidence: 48%
“…This suggests that there may be no specific antigen that plays a role in the development of pulmonary MALT lymphoma. In contrast, restricted usage of the VH fragment has often been observed in MALT lymphomas at various other sites including the stomach (VH3-30 or VH3-23) [12], salivary gland (VH1-69) [18], thymus (VH3-30 or VH3-23) [19], ocular adnexae (VH1-2 or VH4-34) [20], and skin (VH1-69 or VH4-59) [21]. Many of these MALT lymphomas show an associations with a distinctive chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the clonal origin of the disease, a LSA specific immunosignature was identifiable. In humans, certain variable region genes are prevalent in LSA [3234] and superantigens are LSA associated [35], raising the possibility that the immunosignature is that of a causal immunological insult. Proteomic studies in humans have identified distinct protein expression profiles that are informative not only for LSA, but clinical subtype [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…A t(12;21)(q13;q22) has been detected in one patient [38]. Gene expression studies using cDNA microarrays revealed that cases of cutaneous follicle center lymphoma have a germinal center cell signature [39,40] and show hypermutated immunoglobulin variable genes with frequent use of the VH1-69 and VH4-59 segments [41].…”
Section: Molecular Geneticsmentioning
confidence: 99%